Dada : recueil littéraire et artistique (voortzetting van: Cabaret Voltaire : recueil littéraire et artistique (titel varieert: 'Anthologie dada' (nos.4/5); 'Bulletin dada' (no.6); 'Dadaphone' (no.7); 'Dada au grand air ; Der Sängerkrieg in Tirol (no.8)) - Tzara, Tristan (Zürich : Mouvement DADA, 1917)
Edited by Tristan Tzara, was the premier publication of international Dadaism, following the movement from Zürich to Paris before dissolving with Tzara's split with André Breton and the emergence of Surrealism. (Blue Mountain Project : Historical Avant-Garde Periodicals for Digital Research)
Facsimile.1981
Online: International Dada Archive: http://sdrc.lib.uiowa.edu/dada/dada/index.htm en https://digital.kunsthaus.ch/viewer/toc/25068/1/-/ en https://bluemountain.princeton.edu
Frans
Tijdschriften
Keywords: dadaïsme